Receding height of water droplet in the film boiling regime - Illias, Suhaimi; Hussain, Suhaila; Rosman, N A; Abdullah, Nadiah Syafiqah; Shaiful, Mohamad Shaiful Ashrul; Omar, Mohd Nazri; Ismail, K A; Ani, Mohd Hanafi (Institute of Physics Publishing, 2019)
The purpose of this research was to study and investigate the receding height of water droplet after it impinged on hot aluminum surface. On top of that, we also investigated the relationship between this receding phenomenon and residence time of water droplet. Degassed and distilled water was used as a droplet. The droplet diameter was maintained at 4.0 mm and the impact height was set to be around 65.0 mm corresponding to impact velocity of 1.129 m/s. The liquid temperature was kept around 16 °C corresponding to liquid subcooling of ∆Tsub = 84 K. The material selected in this experiment was aluminum surface. The surface had been polished until it became a mirror polished surface. The dimensions of the material surface were 30.0 mm in diameter and 8.0 mm in height. The phenomena were recorded at 10,000 frames per second using a high speed video camera. As a result, it was observed that the receding height during film boiling regime was almost similar to each other even the surface temperature was different. Furthermore, the residence time during the experiment was also close to the theoretical calculation.